2022
DOI: 10.1038/s41598-022-24578-8
|View full text |Cite
|
Sign up to set email alerts
|

High electrolyte uptake of MXene integrated membrane separators for Zn-ion batteries

Abstract: The recent development of separators with high flexibility, high electrolyte uptake, and ionic conductivity for batteries have gained considerable attention. However, studies on composite separators with the aforementioned properties for aqueous electrolytes in Zn-ion batteries are limited. In this research, a polyacrylonitrile (PAN)/bio-based polyurethane (PU)/Ti3C2Tx MXene composite membrane was fabricated using an electrospinning technique. Ti3C2 MXene was embedded in fibers and formed a spindle-like struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…DPH25 displayed a superior electrolyte uptake of ∼2213% (mean value), which is approximately 10 times higher than that of the PP separator. Lower electrolyte uptake indicates incomplete filling of the electrolyte in the separator pores, and thus results in reduced Li + diffusivity. , A number of recent studies have reported ultrahigh electrolyte uptakes ( > 2000%) utilizing functional materials (e.g., MXene or cellulose acetate). , It is worth noting that the carbonate electrolyte does not have any adverse effect on the DPH25 separator. The structure of DPH25 remains mainly unchanged even after immersion in the electrolyte (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…DPH25 displayed a superior electrolyte uptake of ∼2213% (mean value), which is approximately 10 times higher than that of the PP separator. Lower electrolyte uptake indicates incomplete filling of the electrolyte in the separator pores, and thus results in reduced Li + diffusivity. , A number of recent studies have reported ultrahigh electrolyte uptakes ( > 2000%) utilizing functional materials (e.g., MXene or cellulose acetate). , It is worth noting that the carbonate electrolyte does not have any adverse effect on the DPH25 separator. The structure of DPH25 remains mainly unchanged even after immersion in the electrolyte (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…A significant electrolyte uptake is crucial for electrodes because the volume of liquid electrolytes situated between the electrode active materials can influence the internal ionic resistance of batteries. 52 According to these outcomes, it can be concluded that incorporating the optimum amount of MoS 2 not only improves the conductivity of the MoS 2 @CMO composite electrodes but also facilitates the transportation of Li-ions and electrons during the cycling process. This improvement significantly enhances the electrochemical performance of the electrodes.…”
Section: Acsmentioning
confidence: 95%
“…9,50 Furthermore, to measure the uptake of the electrolyte solution, the CMOMS-7 electrodes were weighed and immersed in the 1 M LiPF 6 electrolyte solution for 2 h. The extra electrolyte on the electrode surface was wiped off using tissue paper, and then, the electrodes were weighed again. The electrolyte uptake was determined using the following equation 51,52…”
Section: Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an indispensable component in batteries and the path for ion transport, the separator controls the transport of cations and anions, which is of great importance for the charge–discharge properties. 24 Accordingly, the design and construction of functional separators is an efficient strategy to regulate the ion transport in batteries. In the case of zinc anodes, separators with a high Zn 2+ transference number ( t Zn 2+ ) are beneficial for mitigating the interface ion concentration gradient and promoting the transport of Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%